Analisis Filogenetik Apis dorsata (Fabricius 1793) Bedasarkan Gen Chytochrome Oxidaxe I (COI) - Delima, Nur; Masrianih, Masrianih; Trianto, Manap; Windarsih, Yulia; Buntu, Amalia; Dhafir, Fatmah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
Apis dorsata is a giant honeybee species distributed across South and Southeast Asia. Phylogenetic analysis is used to illustrate the evolutionary relationships of organisms through a phylogenetic tree. This study aims to describe the genetic relationships of A. dorsata based on the cytochrome oxidase I (COI) gene. Sampling was conducted using an exploratory method in various regions, followed by DNA isolation, DNA amplification, sequencing, and bioinformatics analysis using GeneStudio, DNASTAR, MESQUITE, and MEGA 11. The results show that phylogenetic analysis using the Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods produced a phylogenetic tree that clearly depicts evolutionary relationships. A. dorsata from Central Sulawesi is more closely related to other A. dorsata species within the same internal cluster, while other species are separated. These findings reveal a clear pattern of genetic relationships among A. dorsata populations.